INOVASI PEMBELAJARAN BLENDED LEARNING DALAM PENDIDIKAN MATEMATIKA - Baharuddin (Jurnal Citra Pendidikan, 2025)
Learning mathematics in the digital era demands innovation that is able to integrate technology and pedagogical approaches that suit the needs of the 21st century. One of the rapidly growing approaches is blended learning, which is a learning model that combines the advantages of face-to-face learning with online learning. This article aims to analyze the implementation of blended learning in mathematics education through a literature study approach. The results show that blended learning can improve students' concept understanding, learning motivation, and mathematical literacy. An effective blended learning design includes interactive face-to-face components, self-directed online learning, and technology-based formative assessment. However, the implementation of blended learning also faces challenges, such as teacher readiness and student discipline. Therefore, blended learning innovation needs to be implemented systematically with the support of education policy, teacher training, and adequate digital infrastructure. This research contributes to formulating the design direction of mathematics learning that is more flexible, participatory, and contextual in the future.